2014
DOI: 10.1001/jamaoto.2014.1675
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hazardous Events in Olfactory-Impaired Patients

Abstract: Increased level of olfactory impairment portends an increased risk of experiencing a hazardous event. Risk is further impacted by individuals' age, sex, and race. These results may assist health care practitioners in counseling patients on the risks associated with olfactory impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
6
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 15 publications
3
86
6
2
Order By: Relevance
“…In another study, 32 impaired olfaction was a risk factor for certain injuries because normosmia allows early detection and avoidance of potentially hazardous situations, such as cooking or house fires, delayed detection of gas leaks, and exposure to or ingestion of toxic substances. 32 In our study, higher physical activity was associated with better olfactory function; therefore, we can conclude that it is another argument for recommending physical activity. Accordingly, DISCUSSION Regular physical activity improves metabolic control and reduces the risk of chronic diabetic complications.…”
Section: Methodssupporting
confidence: 53%
“…In another study, 32 impaired olfaction was a risk factor for certain injuries because normosmia allows early detection and avoidance of potentially hazardous situations, such as cooking or house fires, delayed detection of gas leaks, and exposure to or ingestion of toxic substances. 32 In our study, higher physical activity was associated with better olfactory function; therefore, we can conclude that it is another argument for recommending physical activity. Accordingly, DISCUSSION Regular physical activity improves metabolic control and reduces the risk of chronic diabetic complications.…”
Section: Methodssupporting
confidence: 53%
“…Individuals with olfactory dysfunction are 2 to 3 times more likely to experience a hazardous event than individuals with normosmia [64], including burning or starting a fire while cooking, inability to smell smoke or a natural gas leak, or ingesting spoiled foods or toxic substances. Preventive efforts that can minimize these hazardous events among individuals with olfactory dysfunction include using smoke detectors and creating fire escape plans, dating foods, reading food labels, as well as following safe food handling to avoid ingesting spoiled foods.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly the authors found that 19.0% of patients with normal olfactory testing had at least 1 hazardous event. Risk of hazardous events appears to be statistically higher in patients over the age of 65, women, and African-Americans [72].…”
Section: Managementmentioning
confidence: 94%